O outro na cidade: deficiência, acessibilidade e saúde em Presidente Prudente-SP - Alves, Natália Cristina [UNESP] (2015)
This research aims to study the context of the accessibility to the health system by the disabled people in Presidente Prudente - SP. Based on the qualitative research methodology and interviews through the thematic oral history. As a primary result from the 2010 Census conducted by the Brazilian Institute of Geography and Statistics (IBGE), it was possible to detect some geographical characteristics of the distribution and spatial differences of these subjects, such as its greater concentration in the peripheral areas of the city. By field work and interviews, it was analyzed what were the accessibility context of people with physical disabilities living at these outlying areas considering the accessibility barriers at the cities, as well as the dimensions aiming a specific context health for this population. These results allowed assessing that there is a need for urban planning that thinks about social inclusion and urban space in this city, as well as the needs for an intersectoral approach, supplying services in support of this people in their context. Therefore, we consider that accessibility to health system can be seen as a way of understanding the processes of production and reproduction of contemporaneous urban spaces, especially because the use and appropriation of the city can reveal many sort of spatial inequalities and social exclusion. This issue can be seen when looking at accessibility from people with motor disabilities that have a space-time relationship and different moves of others, and this difference often is characterized by its representation as the other ones in the city